Promises to keep : technology, law, and the future of entertainment - Fisher, William W. (Stanford Law and Politics, 2004)
"During the past fifteen years, changes in the technologies used to make and store audio and video recordings, combined with the communication revolution associated with the Internet, have generated a wide array of new ways in which music and movies can be produced and distributed. Both the creators and the consumers of entertainment products stand to benefit from the new systems. If the available technologies were exploited fully, the costs of audio and video recordings would drop sharply, the incomes of artists would rise, many more artists could reach global audiences, the variety of music and films popularly available would increase sharply, and listeners and viewers would be able to participate much more easily in the shaping of their cultural environments. Sadly, we have failed thus far to avail ourselves of these opportunities. Instead, much energy has been devoted to interpreting or changing legal rules in hopes of defending older business models against the threats posed by the new technologies. These efforts to plug the multiplying holes in the legal dikes are failing and the entertainment industry has fallen into crisis." "This book chronicles how we got into this mess and presents three alternative proposals - each involving a combination of legal reforms and new business models - for how we could get out of it."--BOOK JACKET.